Voice in The “Long 20th Century”: From Mechanical to Electrical Aurality - Larrue, Jean-Marc (Recherches sémiotiques / Semiotic Inquiry, 2015)
The use of microphones in theatre today is so common that it is hard to believe how recent this practice is and, more importantly, that it has provoked such long standing and fierce resistance. The fact is that the theatre, which very quickly integrated the electric lamp (at the end of the 19th century) into its technical arsenal, waited more than a century before resorting to microphones to relay the voices of the actors. Technological imperfections alone are not sufficient to explain this deferment since, between the emergence of the first sound reproduction technologies in the late 1870s (microphone, phonograph, telephone) and the 21st century, four distinct media have enjoyed considerable success on account of these technologies : records, radio, cinema and television. This article argues is that such delay was due to an ideological positioning by which the theatre tried to affirm its ontological superiority over the other media practices by establishing itself as the ultimate refuge of “authenticity” by virtue of the simultaneous – and non-technologically mediated – presence of the actor and the spectator in a single space. In this context, the human voice of theatre took on a highly symbolic value, that of unadulterated authenticity, a value which seemed perverted everywhere else.